COVID-19: Current Status and Future Prospects - Leggat, Peter; Frean, John; Blumberg, Lucille (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
On 11 March 2020, the World Health Organization declared COVID-19 a global pandemic, and the disease now affects nearly every country and region. Nearly 18 months later, COVID-19, caused by SARS-CoV-2, continues to present significant challenges to health systems, public health, and the economy of countries across both hemispheres. The morbidity and mortality of the infection caused by SARS-CoV-2 has been significant, and various waves of disease outbreaks initially overwhelmed hospitals and clinics in many countries and continue to do so. This influences everyone, and public health countermeasures have been dramatic in terms of their impact on employment, social systems, and mental health. This Special Issue collection follows on from the Special Issue "COVID-19: Current Challenges and Future Perspectives" and provides an avenue for authors from various disciplines to provide feedback on the response to and our future global preparedness for COVID-19, as well as to disseminate critical information about SARS-CoV-2 and the associated COVID-19 pandemic.